Language and cultural values exploration of traditional songs in Malakan Ethnic, Eastern Indonesia - Jama, Karolus Budiman; Menggo, Sebastianus (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
The present research undertakes a cultural analysis of ethnic verses and songs from Malakan to uncover their underlying philosophical thought. Understanding these works' fundamental principles and concepts is essential to convey their valuable knowledge, which ultimately shapes and reinforces values in future generations. Cultural-linguistic theory by Sharifin (2021) was utilized to find out if Malakan ethnic song verses include cultural features. This descriptive-qualitative study method used observation, in-depth interviews, documentation, and Focus Group Discussions with 40 participants from eight communities from July to September 2023. The findings indicate that the auditory elements of lyrics, words, phrases, and clauses serve as a means of conveying the cultural values of the Malakan people when singing four traditional songs as a component of their daily lives. In addition, several values were derived from the meaning of the four-song lyrics, including patience, responsibility, commitment, resilience, harmony, togetherness, sacrifice, empathy, and sympathy, which ultimately serve as a reference for human behavior in the Malakan community. The findings suggest that storing traditional artworks linked to poetry and musical works is advisable. Through the utilization of poetry and musical compositions, people could find cultural components that can be reused as indigenous content for the study of cultural arts and local languages.